Media and Resources Development of Android Based Interactive Digital Textbook in Nonformal Education - Nengsih, Yanti Karmila; Handrianto, Ciptro; Nurrizalia, Mega; Waty, Evy Ratna Kartika; Shomedran, Shomedran (Journal of Nonformal Education, 2022)
The development of Android-based interactive digital textbooks is one of the means which is expected to help improve students' understanding of concepts in the learning process. Interactive digital books can be used as a tool by lecturers in the learning process in the classroom so that lecturers do not only use conventional learning methods in the learning process. In line with the times, many lecturers, students and even the public generally access all information via digital. This paper aims to create an Android-based interactive digital textbook as media and resources for Nonformal Education (PLS) learning tools. The ADDIE Model (Branch, 2009) is used in this study. It consists of five stages: analysis, design, development, implementation, and evaluation. The research starts with a literature review and need`s assessment of 47 students for an Android-based interactive digital textbook, followed by a textbook draft. After compiling the Android-based interactive digital textbook, it is validated by three experts: content/material expert, presentation expert, and Indonesian language expert. After being evaluated by three experts, the draft of an Android-based interactive digital textbook is revised to accommodate individual and small group testing. In the outstanding category, interactive digital media textbooks and PLS learning resources based on Android received a total score of 146 (91.25%) from three expert validators. This research shows that interactive digital textbooks are very practical, with a practicality percentage of 83.33% for one-to-one and 83.16% for small groups. The android-based PLS media and learning resources are valid and valuable. Due to the lack of availability of media teaching materials and learning resources in out-of-school education, the presence of Android-based textbooks that can be accessed anywhere and at any time can help both lecturers and students understand media materials and learning resources outside of school.